A ferrosilicon ingot mold release agent and a demoulding method based on the release agent
By using a release agent layer composed of microsilicon powder and water, combined with the microsilicon powder and silicon particles to lay the gaps in the ingot mold, the adhesion and iron leakage problems between the ferrosilicon ingot mold and the gray cast iron ingot mold in the automated linear casting system are solved, and efficient mold release and resource recycling are achieved.
Patent Information
- Application Number
- CN202411808025.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, in the automated linear casting system, the ferrosilicon ingot die and the gray cast iron ingot die are prone to stick together, resulting in difficulty in demolding and serious damage to the ingot die, and there is a problem of iron leakage in the joint ingot die gap.
A ferrosilicon ingot mold release agent is used, which consists of component A composed of microsilicon powder and water, and component B composed of microsilicon powder and silicon particles. Component B is used to lay the gaps of the ingot die, and component A is sprayed on the surface of the ingot die to form a release agent layer, reducing the direct contact between the molten iron and the ingot die, and preventing adhesion and leakage of iron.
It effectively solves the adhesion problem between the ferrosilicon ingot die and the gray cast iron ingot die, reduces the damage and iron leakage of the ingot die, extends the service life of the ingot die, improves the production efficiency, and realizes the recycling of resources.
Smart Images

Figure BDA0005179804070000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ferrosilicon ingot mold demoulding, and particularly relates to a ferrosilicon ingot mold demoulding agent and a demoulding method based on the demoulding agent. Background Art
[0002] At present, most ferroalloys are cast using ingot molds. Ingot mold casting can control the appearance quality of the product, that is, to ensure that the product grades can be effectively distinguished and the product numbers are not easily confused. At the same time, it is convenient for finishing unqualified iron, and is suitable for almost all types of ferroalloy casting methods. At present, there are still major technical defects in automated casting. Ferrosilicon cast on ingot molds needs to be cooled to a normal state before demolding, and mold sticking is common, which hinders automated iron tapping and reduces production efficiency.
[0003] Chinese utility model patent CN208696260U discloses a mold for rare earth magnesium ferrosilicon alloy that is easy to demold, including a casting mold tray and a demolding tray. A surface of the casting mold tray is provided with a rectangular casting groove; a surface of the rectangular casting groove is provided with casting holes arranged in a rectangular pattern; a surface of the casting hole is provided with a stepped circular hole; the stepped circular hole includes a demolding head hole and a guide circular hole; a side of the casting mold tray is provided with a guide groove; and a surface of the casting mold tray is fixed with a plurality of fixed support rods. The mold is used to produce multiple alloy blocks through the casting mold tray. After the production is completed, the demolding tray, guide connecting rod, spring and demolding head only need to be turned over and all demolding heads of the demolding tray are pressed down by a pressure device to eject the metal block from the casting hole to quickly complete the demolding, which solves the problem of low demolding rate of existing trays that require manual demolding one by one. However, it is not suitable for the production of large ingot molds.
[0004] Chinese invention patent CN109702141B discloses a high-efficiency ferrosilicon alloy ingot mold release agent, which includes the following components: a sodium-containing compound, silicon micropowder, and water. The sodium-containing compound can generate sodium silicate with silicon micropowder under the condition of heating in an aqueous solution. The sodium-containing compound is sodium hydroxide. The weight component ratio of the ferrosilicon alloy ingot mold release agent is: sodium hydroxide: silicon micropowder: water in the range of 0.05-0.3:0.05-0.3:1. In actual use, the release agent has a simple formula and is easy to prepare. It will form a layer of gel on the surface of the ingot mold, thereby blocking the direct contact between the molten iron and the ingot mold. When the molten iron is cooled and solidified, the cooled ferroalloy can be easily separated from the ingot mold. In addition, the solid waste silicon micropowder generated in the ferroalloy production process is effectively used as a raw material to prepare the release agent, which does not increase the cost of ferroalloy production and has a good actual use effect.
[0005] After using the ingot mold of the automated linear pouring system, on the one hand, when the smelted molten iron is poured on the ingot mold and cooled and then demolded, it is found that the ferrosilicon is bonded to the ingot mold over a large area, making it difficult to separate the ferrosilicon from the ingot mold. At the same time, the internal damage to the ingot mold is particularly serious during the beating process. On the other hand, after pouring, a large amount of heat released when the silicon solution solidifies is absorbed by the ingot mold, and a small amount of heat is conducted to the air through thermal radiation. The ingot mold will be eroded and penetrated by the high-temperature fluid, and the ingot mold will break during the cooling process. This will not only greatly shorten the service life of the ingot mold, but also bring impurity elements into the ferrosilicon when the ingot mold is eroded and eroded, affecting the quality of the product. As the temperature of the ingot mold itself continues to increase, the thermal expansion stress makes the gap between the ingot mold and the ingot mold larger and larger, resulting in an increase in the frequency of iron leakage from the ingot mold, resulting in frequent waste of ferrosilicon. At the same time, the leaked molten iron burns equipment and facilities, resulting in a high equipment failure rate and a large consumption of spare parts. This problem has become a key constraint in the production process of large furnace ferroalloys, greatly affecting the production progress.
[0006] However, the above-mentioned release agents are still unable to solve this problem. Therefore, it is urgent to improve the existing release agents and demoulding methods to solve the problems of demoulding difficulty and iron leakage. Summary of the invention
[0007] In view of the above-mentioned problems existing in the prior art, the present invention provides a ferrosilicon ingot mold release agent and a demolding method based on the release agent, which solves the problem that the ferroalloy ingot mold and the gray cast iron ingot mold of the existing automated linear casting system are easily adhered to each other and cannot be effectively demolded, thus causing damage to the ingot mold, and at the same time solves the problem of iron leakage and burning of equipment due to gaps in the combined ingot mold.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] The invention provides a ferrosilicon ingot mold release agent, which comprises component A; the component A consists of microsilicon powder and water.
[0010] Furthermore, the mass ratio of microsilica powder to water in component A is 0.01-0.025:1.
[0011] Furthermore, the ferrosilicon ingot mold release agent also includes component B; the component B consists of microsilicon powder and silicon particles.
[0012] Furthermore, the mass ratio of microsilica powder to silicon particles in component B is 1-3:3.
[0013] In the present invention, the mass ratio of microsilica powder and silicon granules is determined according to the burning condition of the gap joints of the ingot mold. Specifically, if the burn loss is ≤5%, the microsilica powder and silicon granules are mixed in a mass ratio of 1:3; if the burn loss is 5%≤≤20%, the microsilica powder and silicon granules are mixed in a mass ratio of 2:3; if the burn loss is 20%, the microsilica powder and silicon granules are mixed in a mass ratio of 1:1.
[0014] Furthermore, the particle size of the microsilica powder is 1-3 mm; the particle size of the silicon particles is 1-5 mm.
[0015] The present invention also provides a method for demolding a ferrosilicon ingot mold based on any of the above-mentioned ferrosilicon ingot mold release agents, comprising the following steps:
[0016] (1) First, add water and silicon powder into a release agent preparation tank, stir and mix thoroughly to obtain component A; or take silicon powder and silicon particles and mix thoroughly to obtain component B;
[0017] (2) using component B to pave the gap of the ingot mold, and then spraying component A, and stopping spraying after the surface temperature of the ingot mold drops to a suitable temperature, so as to form a release agent layer on the surface of the ingot mold;
[0018] (3) Pour the smelted ferrosilicon molten iron onto the ingot mold. After the ferrosilicon molten iron cools down, separate the ferrosilicon ingot mold to complete the entire demoulding process.
[0019] In the present invention, component B is used to pave the mold gap of the combined ingot mold. During the spraying process, the water in component A acts on the padded ingot mold so that the release agent as a whole becomes a binder that tightly bonds the two ingot molds, thereby reducing the burning rate of the ingot mold gap by molten iron during pouring.
[0020] In addition, by spraying component A on the surface of the ingot mold, the temperature of the ingot mold can be reduced from (350℃-450℃) to (150℃-200℃), so that a layer of micro-silicon powder oxidation thin mold protective layer can be formed on the ingot mold during cooling and quenching, thereby isolating the direct contact between the molten iron and the ingot mold. When the molten iron is cooled, the cooled silicon-based alloy can be easily separated from the ingot mold intact.
[0021] Furthermore, the ingot mold is a grey cast iron ingot mold.
[0022] Furthermore, the dosage of component B is determined according to the size of the ingot mold and the gap depth, specifically, the padding height is 1-5 cm and the width is 2-10 cm.
[0023] Furthermore, in step (2), when the surface temperature of the ingot mold drops to 150-200° C., spraying is stopped.
[0024] Furthermore, the thickness of the release agent layer is ≤3 mm.
[0025] Furthermore, in step (3), the ferrosilicon ingot mold is separated from the mold tail to the mold head using a demoulding machine breaker hammer.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The use of the release agent of the present invention using component A (microsilica powder and water) effectively solves the problem that the large ingot mold of the existing automated linear casting system is easy to adhere to the gray cast iron ingot mold and cannot be effectively demolded, thereby causing serious damage to the ingot mold;
[0028] (2) The simultaneous use of component A (microsilica powder and water) and component B (microsilica powder and silicon particles) not only solves the problem of easy adhesion between the ferroalloy and the gray cast iron ingot mold, but also solves the problem of iron leakage and burning of the combined ingot mold gap, effectively extending the service life of the ingot mold and reducing the cost of use;
[0029] (3) In addition, the present invention uses microsilicon powder, a byproduct of the production process of ferrosilicon alloy, to effectively reduce the treatment of solid waste and achieve the recycling of resources;
[0030] (4) The demoulding method is simple and convenient to operate, and the demoulding process is smooth. It not only improves the production efficiency of the ferroalloy casting system, but also greatly saves the labor intensity of personnel and the waste of ingot mold replacement in the original production process, providing strong support for the continuous production operation of large-scale ferroalloy continuous production enterprises with electric arc furnaces. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited.
[0032] The equipment information used in the present invention is shown in Table 1; the raw material information used is shown in Table 2.
[0033] Table 1
[0034]
[0035] Table 2
[0036] Serial number Device Name factory Specification 1 Microsilica fume Inner Mongolia Low Carbon Ferroalloy Technology Co., Ltd. Particle size 1-3mm 2 Silicon particles Inner Mongolia Low Carbon Ferroalloy Technology Co., Ltd. Particle size 1-5mm
[0037] First, prepare component A and component B: take the raw materials according to the above ratio, and stir and mix them thoroughly to obtain component A and component B, which are set aside.
[0038] In some schemes of the present invention, when a single ingot is used for demolding of ferrosilicon alloy preparation, component A (a mixture of microsilicon powder and water) is directly sprayed, and the surface temperature of the ingot mold drops from (350°C-450°C) to (150°C-200°C), so that a layer of microsilicon powder oxide thin mold protective layer (i.e., a release agent layer, with a thickness of ≤3mm) is formed on the ingot mold during cooling and quenching, thereby isolating the direct contact between the molten iron and the ingot mold. After the molten iron is cooled, a demolding machine breaker hammer is used to separate the ferrosilicon ingot mold from the mold tail to the mold head in sequence to complete the entire demolding process.
[0039] The specific operation process is as follows:
[0040] (1) Mix the silica fume and water in a ratio of 0.01-0.025:1 kg / L. For example, inject 4000 L of clean water into the storage tank, add 60 kg of silica fume, start the mixer and stir it evenly, then stop to obtain component A.
[0041] (2) Move the outlet of the on-site movable pipeline to the center of the first mold, open the valve on the storage box side and the valve at the pipeline nozzle position, start the spray pump, start spraying the release agent, stop the spray pump after spraying, close the valve on the storage box side, confirm that the release agent in the tube has been cleaned at the ingot mold position, and close the valve at the pipeline nozzle position;
[0042] (3) Move the movable part of the pipeline to its original position and fix it with an iron chain. The operator sprays the release agent and then locks the remote control. At the same time, the local operating cabinet is locked and controlled to prevent misoperation.
[0043] In other embodiments of the present invention, in order to solve the problem of iron leakage from the gap of the combined ingot mold, a paving material (component B, a mixture of microsilicon powder and silicon particles) for paving the gap of the ingot mold is provided to reduce the iron leakage phenomenon of the ingot mold. When the combined ingot is used for the demolding of ferrosilicon alloy preparation, component B is used to pave the mold gap of the ingot mold, and then component A (a mixture of microsilicon powder and water) is sprayed. During the spraying process, the water in component A acts on the padded ingot mold so that the demolding agent as a whole becomes a bonding agent that tightly bonds the two ingot molds, reducing the burning rate of the molten iron to the mold gap of the ingot mold during pouring; when the surface temperature of the ingot mold drops from (350℃-450℃) to (150℃-200℃), a layer of microsilicon powder oxidation thin mold protective layer (i.e., demolding agent layer, thickness ≤3mm) is formed on the ingot mold during cooling and quenching, thereby isolating the direct contact between the molten iron and the ingot mold. When the molten iron is cooled, the demolding machine breaker hammer is used to separate the ferrosilicon ingot mold from the mold tail to the mold head in sequence to complete the entire demolding process.
[0044] The specific operation process is as follows:
[0045] (1) Determine the mixing ratio of microsilica powder and silicon particles according to the burn loss at the joint of the ingot mold gap, wherein the burn loss is ≤5%, and the mixture is mixed at a ratio of 1:3; the burn loss is 5%≤≤20%, and the mixture is mixed at a ratio of 2:3; the burn loss is 20%≤1:1, and the mixture is mixed evenly to obtain a bedding material;
[0046] (2) The evenly mixed bedding material is spread in sequence at the joints of the ingot mold gaps to ensure that the bedding gaps are flat and tight (the bedding height is 1-5 cm and the width is 2-10 cm).
[0047] (3) Mix the silica fume and water in a ratio of 0.01-0.025:1 kg / L. For example, inject 4000 L of clean water into the storage tank, add 60 kg of silica fume, start the mixer and stir it evenly, then stop to obtain a release agent.
[0048] (4) Move the outlet of the on-site movable pipeline to the center of the first mold, open the valve on the storage box side and the valve at the pipeline nozzle position, start the spray pump, start spraying the release agent, stop the spray pump after spraying, close the valve on the storage box side, confirm that the release agent in the tube has been cleaned at the ingot mold position, and close the valve at the pipeline nozzle position;
[0049] (5) Move the movable part of the pipeline to its original position and fix it with an iron chain. The operator sprays the release agent and then locks the remote control. At the same time, the local operating cabinet is locked and controlled to prevent misoperation.
[0050] Starting from April 7, 2024, our unit selected three casting lines for comparative tests.
[0051] Example 1
[0052] The patented ZL201910101869.8 release agent was used for the test.
[0053] According to the test of the release agent and demolding method in the embodiment of patent ZL201910101869.8, the new ingot mold had a good initial use effect. After half a month of use, large-area mold sticking appeared in the first mold and the middle mold. At the same time, a viscous gel layer adhered to the bottom of the ferrosilicon, affecting the appearance quality of the product. On June 11, 2024, the two first molds of the casting line were replaced (65 days of use), and on September 18, 2024, the four middle molds of the casting line were replaced (164 days of use).
[0054] Example 2
[0055] Several ratio tests were conducted using microsilica powder and water.
[0056] (1) Microsilica powder and water were mixed in a mass ratio of 0.008-0.01:1 and sprayed on a new ingot mold. After the new ingot mold was used for 5 days, a slight sticking phenomenon occurred. Upon inspection, it was found that due to the small amount of microsilica powder mixed, a protective film on the ingot mold layer could not be formed;
[0057] (2) Continue to increase the proportion of microsilica powder, mix microsilica powder with water at a mass ratio of 0.012-0.015:1, and continue to use it. After one month of use, the first mold sticks to the mold. According to on-site observation of the surface of the ingot mold, it is found that during the spraying process, the release agent is sprayed sequentially from the first mold, and the microsilica powder mixed in the release agent accumulates less at the first mold position. At the same time, the ingot mold is in a continuous operation state, and the buffer time is short (20 to 30 minutes). The protective layer of the first mold is corroded by molten iron, resulting in ferrosilicon sticking to the mold;
[0058] (3) Continue to increase the proportion of microsilica powder and mix microsilica powder with water in a mass ratio of 0.02-0.025:1. Continue to use it. During use, the ingot mold effectively forms a white oxide film layer with a thickness of 3 mm, effectively forming a separation layer, and the separation effect of ferrosilicon and the ingot mold is significant.
[0059] On August 23, 2024, the first mold of casting line No. 4 was replaced (137 days of use). On September 18, 2024, the middle mold of the casting line was burned 5 cm. The ingot mold was in a normal burn state and could continue to be used, which greatly extended the service life of the first mold. At the same time, compared with plan 1, the cost of sodium-containing compounds (sodium hydroxide) was reduced, and the cost was also greatly reduced.
[0060] Example 3
[0061] The tests were conducted without any release agent.
[0062] The tail mold with the longest use period of the ingot mold was used for 44 days on May 21, 2024, and the burn loss reached 25cm.
[0063] Example 4
[0064] In March 2024, the unit had accumulated more than 70 iron leaks from the ingot mold gaps, and the bottom rails and power supply markings were burned, and the ingot mold car assembly frame required more than 8 hours of maintenance each time, which seriously affected the ferrosilicon smelting production and made it impossible to pour molten iron normally.
[0065] In May 2024, microsilica powder and silicon particles (component B) were mixed and paved, and microsilica powder and water (component A) were used to form an ingot mold protective film, so that the gaps in the ingot mold were bonded by component B and component A, effectively preventing the iron leakage from the ingot mold, as follows:
[0066] (1) The mixing ratio of microsilica powder and silicon particles is determined according to the burning loss at the joint of the ingot mold gap, wherein the burning loss is ≤5%, and the mixing ratio is 1:3; the burning loss is 5%≤≤20%, and the mixing ratio is 2:3; the burning loss is 20%≤1:1, and the mixing ratio is uniform to obtain a bedding material; the uniformly mixed bedding material is sequentially spread at the joint of the ingot mold gap to ensure that the bedding gap is flat and tight (the bedding height is 1-5 cm and the width is 2-10 cm);
[0067] (2) The microsilica powder and water are mixed in a mass ratio of 0.02-0.025:1 and sprayed on a new ingot mold. During use, the ingot mold effectively forms a white oxide film layer with a thickness of 3 mm, effectively forming a separation layer.
[0068] In May, there were 15 cases of iron leakage from ingot moulds. In June, after all casting lines of our unit were put into use, there was no iron leakage from ingot moulds, which greatly reduced the impact of equipment damage due to molten iron burning on production efficiency and ensured the normal operation of the casting system in front of the furnace.
[0069] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A ferrosilicon ingot mold release agent, characterized in that: The ferrosilicon ingot mold release agent comprises component A; the component A consists of microsilica powder and water.
2. The ferrosilicon ingot mold release agent according to claim 1, characterized in that The mass ratio of the microsilica powder to water is 0.01-0.025:
1.
3. The ferrosilicon ingot mold release agent according to claim 1 or 2, characterized in that: The ferrosilicon ingot mold release agent also includes component B; the component B consists of microsilicon powder and silicon particles.
4. The ferrosilicon ingot mold release agent according to claim 3, characterized in that: The mass ratio of microsilica powder to silicon particles in the component B is 1-3:
3.
5. The ferrosilicon ingot mold release agent according to claim 4, characterized in that: The particle size of the microsilica powder is 1-3 mm; the particle size of the silicon particles is 1-5 mm.
6. A method for demoulding a ferrosilicon ingot mold based on the ferrosilicon ingot mold release agent according to claim 1 or 2, characterized in that: The following steps are involved: (1) First, add water and silicon powder into a release agent preparation tank, stir and mix thoroughly to obtain component A; (2) spraying component A, and stopping spraying after the surface temperature of the ingot mold drops to an appropriate temperature, thereby forming a release agent layer on the surface of the ingot mold; (3) Pour the smelted ferrosilicon molten iron onto the ingot mold. After the ferrosilicon molten iron cools down, separate the ferrosilicon ingot mold to complete the entire demoulding process.
7. A method for demoulding a ferrosilicon ingot mold based on the ferrosilicon ingot mold release agent according to any one of claims 3 to 5, characterized in that: The following steps are involved: (1) First, water and silicon powder are added to a release agent preparation tank, and the mixture is stirred to obtain component A; at the same time, silicon powder and silicon particles are mixed to obtain component B; (2) using component B to pave the gap of the ingot mold, and then spraying component A, and stopping spraying after the surface temperature of the ingot mold drops to a suitable temperature, so as to form a release agent layer on the surface of the ingot mold; (3) Pour the smelted ferrosilicon molten iron onto the ingot mold. After the ferrosilicon molten iron cools down, separate the ferrosilicon ingot mold to complete the entire demoulding process.
8. The method for demoulding a ferrosilicon ingot mold according to claim 6 or 7, characterized in that: In step (2), spraying is stopped when the surface temperature of the ingot mold drops to 150-200°C.
9. The method for demoulding a ferrosilicon ingot mold according to claim 6 or 7, characterized in that: The thickness of the release agent layer is ≤3 mm.
10. The method for demoulding a ferrosilicon ingot mold according to claim 7, characterized in that: The amount of component B used is determined according to the size of the ingot mold and the gap depth, specifically, the padding height is 1-5 cm and the width is 2-10 cm.
Citation Information
Patent Citations
A high-efficiency silicon-iron alloy ingot mold release agent
CN109702141B
Rare earth ferrosilicomagnesium is mould for alloy convenient to drawing of patterns
CN208696260U